1996
DOI: 10.1152/ajprenal.1996.271.5.f1045
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C stimulates the small-conductance K+ channel in the basolateral membrane of the CCD

Abstract: We have used the patch-clamp technique to study the regulation of the activity of the basolateral small-conductance K+ channel (SK) in the cortical collecting duct (CCD) of the rat kidney. Addition of 50-75 nM calphostin C, an agent which specifically inhibits protein kinase C (PKC), reduced channel activity by 90% in cell-attached patches. In contrast, addition of 1 microM phorbol 12-myristate 13-acetate, a stimulator of PKC, led to addition of "new" K+ channel currents in 9 of 20 patches in the basolateral m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…EP1 receptor‐induced stimulation of calcium influx is independent of PLC activation, indicating that the EP1 receptor may activate a novel type of calcium permeable channel (40) . The increase in intracellular calcium, in association with PKC activation, acts to activate SK channel activity (43) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EP1 receptor‐induced stimulation of calcium influx is independent of PLC activation, indicating that the EP1 receptor may activate a novel type of calcium permeable channel (40) . The increase in intracellular calcium, in association with PKC activation, acts to activate SK channel activity (43) …”
Section: Discussionmentioning
confidence: 99%
“…(40) The increase in intracellular calcium, in association with PKC activation, acts to activate SK channel activity. (43) Evidence is accumulating for a role for integrins and associated signaling pathways in the transduction of a mechanical signal to bone cells, as a result of strain deformation or fluid shear into a biochemical response. (16,44,45) Anti-␤1-integrin antibodies block direct membrane hyperpolarization by 0.33 Hz PIS and the production of transferable membrane hyperpolarization activity, suggesting a requirement for ␤1-integrins upstream of IL-1␤ release.…”
Section: Il-1␤ In Bone Mechanotransductionmentioning
confidence: 99%
“…In the renal K ϩ channels, the role of phosphorylation mediated by protein kinases in the regulation of channel activity has extensively been examined in the basolateral K ϩ channel of proximal tubule cells [4] and the basolateral and apical K ϩ channels in principal cells of CCD [8][9][10][11]. As for the dephosphorylation process, however, only a few papers have suggested that channel activities enhanced by PKA-mediated phosphorylation are inhibited by phosphatasemediated dephosphorylation in the apical K ϩ channel of rat CCD [13] or cloned renal K ϩ channels (ROMK) expressed in Xenopus oocyte [20].…”
Section: Discussionmentioning
confidence: 99%
“…[Japanese Journal of Physiology, 50, [249][250][251][252][253][254][255][256]2000] nase (PKG) in activation of the K ϩ channel in OKP cells [7]. In the principal cell of rat cortical collecting duct (CCD), the basolateral K ϩ channel is activated by PKC [8] and PKG [9], and the apical K ϩ channel, which is responsible for K ϩ secretion, is activated by PKA and inhibited by PKC [10] and Ca 2ϩ /calmodulin-dependent protein kinase II [11]. Apical K ϩ channels in the thick ascending limb of the rat were reported to be activated by PKA [12].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibitory effects of PKC have been observed on inwardly rectifying K + channels in central neurones (Wu & Tang, 1995; Takano et al 1995) and recombinant expression systems (Henry et al 1996). In contrast, PKC has been shown to enhance K + channel activity in cortical collecting duct cells (Lu & Wang, 1996) and accelerate K + channel activation kinetics in pulmonary vascular smooth muscle cells (Smirnov & Aaronson, 1996). The responses of ATP‐sensitive K + channels (K ATP channels) to PKC activation appear to be tissue specific: in arterial smooth muscle cells, K ATP channels are inhibited by PKC (Bonev & Nelson, 1996), whereas in cardiac myocytes PKC causes K ATP activation (Hu et al 1996).…”
Section: Discussionmentioning
confidence: 99%